The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1590/s1415-43662006000200011
|View full text |Cite
|
Sign up to set email alerts
|

Atributos químicos do solo e produtividade do milho afetados por corretivos e manejo do solo

Abstract: RESUMOEste trabalho foi realizado na Fazenda Experimental Lageado, pertencente à Universidade Estadual Paulista-UNESP, Campus de Botucatu, SP, em um Nitossolo distrófico, na safra de 1997/98. Avaliaram-se os efeitos da aplicação de termofosfato magnesiano; termofosfato + calcário e termofosfato + gesso + vinhaça, nas propriedades químicas do solo e na produtividade do milho (Zea mays L.) cultivar XL-345 da Braskalb, cultivado nos sistemas plantio direto e preparo convencional. Foi utilizada a Crotalaria juncea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
0
0
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 2 publications
1
0
0
5
Order By: Relevance
“…For mass of 100 grains, this author finds highest value in minimum tillage and lower value for treatment without tillage. In research conducted by SANTOS et al (2006) in a dystrophic Nitosol, applied magnesium thermophosphate ,thermophosphate + lime and thermophosphate + gypsum + stillage , cultivated in systems no-tillage and conventional no-tillage, was found that conventional no-tillage gave higher grain yield of maize compared to the system notillage, agreeing with the results found by DOMINGUES (2004). ALMEIDA et al (2008) found, after three years of installation of soil management systems, the effects of rotation with green manure, corn or soybean (summer) and beans "winter", that systems of crop rotation, cover crops and management of the soil influence the physical and chemical properties of soil and crop productivity bean, corn and soybeans.…”
Section: Resultssupporting
confidence: 85%
“…For mass of 100 grains, this author finds highest value in minimum tillage and lower value for treatment without tillage. In research conducted by SANTOS et al (2006) in a dystrophic Nitosol, applied magnesium thermophosphate ,thermophosphate + lime and thermophosphate + gypsum + stillage , cultivated in systems no-tillage and conventional no-tillage, was found that conventional no-tillage gave higher grain yield of maize compared to the system notillage, agreeing with the results found by DOMINGUES (2004). ALMEIDA et al (2008) found, after three years of installation of soil management systems, the effects of rotation with green manure, corn or soybean (summer) and beans "winter", that systems of crop rotation, cover crops and management of the soil influence the physical and chemical properties of soil and crop productivity bean, corn and soybeans.…”
Section: Resultssupporting
confidence: 85%
“…Portanto, a identificação de alternativas que possibilitem a melhoria das propriedades químicas do solo em profundidade em pastagens instaladas, partindo da aplicação superficial, sem incorporação, pode viabilizar a permanência e o sucesso deste sistema. A utilização do gesso pode ser uma alternativa para melhoria do ambiente radicular em profundidade (Santos et al, 2006). Por ser um produto mais solúvel é incorporado de maneira fácil ao perfil do solo (Lopes e Guilherme, 2000), proporcionando aumento no suprimento de cálcio e redução da toxidez de alumínio no subsolo (Raij et al, 1998), além do fornecer enxofre para as plantas (Vitti et al, 2008).…”
Section: Introductionunclassified
“…Neste sentido, o gesso pode ser utilizado para melhoria do ambiente radicular em profundidade (Santos et al, 2006). Tal produto é condicionador de solo e possui alta mobilidade no perfil, capaz de disponibilizar os íons Ca 2+ e SO 4 2-em solução e de ser lixiviado, enriquecendo de nutrientes as camadas subsuperficiais e reduzindo a saturação por Al 3+ em profundidade (Alcordo & Rechcigl, 1993).…”
Section: Introductionunclassified